Quality of the nursing care and the psychomotor development of the children under five years old in the Health centre “Virgen Del Carmen” La Era, Lurigancho Chosica - Lima - Espíritu Ramos, Thalia (2019)
Objetive: The objective was to determine the association between quality of nursing care perceived by mothers andpsychomotor development of children under five years old in the “Virgen del Carmen Health Centre- The Era”,Lurigancho. Methods: The methodology was non-experimental, quantitative approach, descriptive-correlationalreach and cross cut. The type of the sample was probabilistic; the sample was composed by 281 children withtheir mothers. Tree instruments were used: Adapted Quality Scale of Nursing Care, Evaluation Guide of 0-30months- Peruvian Test, Evaluation Guide of 3 and 4 years-Brief pattern. Results: The results showed the 89.7%of mothers perceived a high quality, 10% medium and 0.4% lower. Children 0-30 months 97.6% present normalpsychomotor development, 2.4% risk to the disorder of the development. About the 3 and 4 years old children,the 14.8% have a psychomotor development deficit and the 85.2% normal. Conclusions: In conclusions issignificant association between quality of nursing care and evaluation of psychomotor development (p = .000).